Investigating Molluscum Contagiosum Virus Protein MC008 and its Effect on Inflammatory Signalling - Phelan, Thomas (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2023)
Molluscum contagiosum virus (MCV) is a human-adapted poxvirus that causes a common, persistent, yet mild infection characterized by distinct, contagious, papular skin lesions. These lesions are notable for having little or no inflammation associated with them and can persist for long periods without an effective clearance response from the host. Like all poxviruses, MCV encodes potent immunosuppressive proteins which perturb innate immune pathways involved in virus sensing, the interferon response and inflammation which collectively orchestrate anti-viral immunity and clearance. Our initial investigation focused on an interaction with the E3 ligase, TRIM32, a protein shown to be involved in cGAS-STING sensing of DNA. This interaction was identified from analysis of MC008 co-purifying proteins by mass spectrometry prior to PhD project commencement. However, we were unable to discern a direct mechanism of MC008 inhibition through this protein. Since several innate immune pathways converge at common signalling nodes, we investigated further downstream. One key node is the regulator of canonical nuclear factor kappa B (NF-κB) activation, NF-κB essential modulator (NEMO). In this thesis, we report that the MCV protein MC008 inhibits NF-κB through its interaction with NEMO, disrupting its early ubiquitin-mediated activation and subsequent downstream signalling. MC008 is the third NEMO-targeting inhibitor to be described in MCV to date, with each inhibiting NEMO activation in distinct ways, highlighting a strong selective pressure to evolve multiple ways of disabling this key signalling protein.
APPROVED
Keywords: NEMO; Innate immunity; Molluscum contagiosum; MC008; NF-κB